Unveiling Learners’ Foreign Language Speaking Anxiety Factors: A Systematic Literature Review - Ananda Siti Khoirunnisa; Yeti Mulyati; Yulianeta Yulianeta; Syihabuddin Syihabuddin (SAWERIGADING, 2026)
This systematic literature review synthesizes empirical evidence from forty Scopus-indexed studies published between 2015 and 2025. This study aims to build comprehensive understanding of factors triggering foreign language speaking anxiety and patterns of these behavioral manifestations. This study follows systematic PRISMA 2020 guidelines with procedures of identification, screening, analysis, and thematic coding of selected studies. Analysis results indicate that foreign language speaking anxiety emerges from six primary thematic domains, namely psychological dispositions and self-belief systems, social-affective pressures and identity concerns, linguistic and communicative competence constraints, performance and evaluation demands, pedagogical practices and instructional design, and contextual-technological conditions. The most frequently identified factor in selected studies was social-affective factors across thirty-one studies. Behavioral manifestations include speech disruption patterns, avoidance behaviors, affective and physiological responses, technology-mediated adaptations, and cognitive interference. The findings of this study underscore that foreign language speaking anxiety emerges through dynamic interactions between internal vulnerabilities and external contextual conditions. This produces a thematic framework for conceptualizing foreign language speaking anxiety more comprehensively. These evidence-based implications support efforts to enhance foreign language learners' speaking abilities. AbstrakTinjauan literatur sistematis ini menyintesis bukti empiris dari empat puluh studi terindeks Scopus yang diterbitkan antara tahun 2015 dan 2025. Penelitian ini bertujuan untuk membangun pemahaman yang komprehensif tentang faktor-faktor pemicu kecemasan berbicara bahasa asing dan pola dari manifestasi perilaku tersebut. Penelitian ini mengikuti pedoman PRISMA 2020 yang sistematis dengan prosedur identifikasi, penyaringan, analisis dan pengodean tematik studi terpilih. Hasil analisis menunjukkan bahwa kecemasan berbicara bahasa asing muncul dari enam domain tematik utama yakni disposisi psikologis dan sistem kepercayaan diri, tekanan sosial-afektif dan masalah identitas, kendala kompetensi linguistik dan komunikatif, tuntutan kinerja dan evaluasi, praktik pedagogis dan desain instruksional, dan kondisi kontekstual-teknologi. Faktor paling banyak teridentifikasi dalam studi terpilih adalah faktor sosial-afektif sebanyak tiga puluh satu studi. Manifestasi perilaku termasuk pola gangguan berbicara, perilaku penghindaran, respons afektif dan fisiologis, adaptasi yang dimediasi teknologi, dan interferensi kognitif. Temuan penelitian ini menggarisbawahi bahwa kecemasan berbicara bahasa asing muncul melalui interaksi dinamis antara kerentanan internal dan kondisi kontekstual eksternal. Hal ini menghasilkan kerangka tematik untuk mengonseptualisasikan kecemasan berbahasa asing lebih mendalam. Implikasi berbasis bukti empiris ini mendukung upaya  peningkatan  kemampuan berbicara pemelajar bahasa asing.